Fluorination Modification of Methyl Vinyl Silicone Rubber and Its Compatibilization Effect on Fluorine/Silicone Rubber Composites - Xing, Shuwen; Yu, Chuhui; Ding, Lei; Li, Shuaiqi; Pan, Gao; Jin, Mengyu; Liu, Li; Wen, Shipeng (ACS omega, 2024)
Among numerous rubbers, high-performance rubber composites can be obtained by mixing fluororubber (FKM) with excellent oil resistance and silicone rubber (SiR) with excellent low-temperature resistance. While the difference in polarity between these two kinds of rubbers leads to a reduction in the properties of the composites. To solve the compatibility problem between the two-phase interfaces in FKM/SiR composites, in this research, fluorinated silicone rubbers (MVQ-g-PFDT) of methyl vinyl silicone rubber (MVQ) grafted with 1H,1H,2H,2H-perfluorodecanethiol (PFDT) were prepared via a facile and efficient thiol–ene click reaction, which was then added into FKM/SiR composites. The results showed that the fluorine-containing side chains could effectively inhibit the low-temperature crystallization phenomenon of silicone rubber and further broaden its application ranges in low-temperature environments. The properties of FKM/SiR composites with the addition of MVQ-g-PFDT were significantly improved, with the highest tensile strength of 14.1 MPa and the lowest mass change rate of 6.71% after 48h immersion at 200 °C in IRM903 oil. Additionally, the hydroxyl groups between the fluorine-containing side chains of MVQ-g-PFDT and the surface of silica facilitate the enhancement of the uniform dispersion of fillers. Atomic force microscopy (AFM) characterization results showed a distinct enhancement of the compatibility between the two phases of FKM and SiR. This work would provide further insight into efforts to improve compatibility between rubbers with widely different polarities.